Scheduling component replacement for timely execution in dynamic systems. (22nd January 2013) - Romero, Julio Cano; García‐Valls, Marisol
SUMMARY Timely run‐time software replacement techniques are a corner stone for reconciling real‐time systems development and dynamic behavior. Typical real‐time systems do not consider dynamic behavior because it deeply challenges predictability and timeliness. Current efforts are starting to merge the safe and predictable execution with a controllable level of dynamicity by imposing a set of bounds and limitations to the system dynamic behavior. One of the obstacles for this is how to time‐bound the different operations required to effectively implement component replacement. In this paper, the main challenges for this problem are identified, and a model to ensure that components can be replaced at run time preserving the temporal properties of the system is provided that also avoids failures in replacements. A real example and simulations of our replacement model are provided that validate the presented ideas. Copyright © 2013 John Wiley & Sons, Ltd.